Men, relationships and partner-initiated break-ups: A narrative analysis - John L Oliffe; Mary T Kelly; Gabriela Gonzalez Montaner; David Kealy; Zac E Seidler; John S Ogrodniczuk; Paul Sharp; Simon M Rice (Health Psychology Open, 2022)
For men, significant risks associated with partner-initiated break-ups include domestic violence, mental health challenges and difficultly with life transition. This narrative analysis study shares three storylines drawn from interviews with 25 men who experienced a partner-initiated break-up. Ill equipped to stay or to initiate leaving narratives positioned participants as conflict averse, lacking agency and withdrawing emotionally from the partnership and its demise. Victims of circumstance narratives included men who engaged in cyclic arguments and ongoing power struggles with partners, a pattern that often amplified conflict after the break-up. Transitioning these two impasse narratives were some participants whose Accountability and growth storylines highlighted their introspective self-work, aided by resources including professional help to deconstruct, understand, and adjust their behaviours. Making connections to masculinities theory, these findings suggest that tailored interventions, including narrative therapy, might usefully interrupt impasse narratives to aid men’s development and healthful transitions through partner-initiated break-ups.